2011
DOI: 10.1002/mds.23829
|View full text |Cite
|
Sign up to set email alerts
|

The Movement Disorder Society Evidence‐Based Medicine Review Update: Treatments for the motor symptoms of Parkinson's disease

Abstract: The objective was to update previous evidence-based medicine reviews of treatments for motor symptoms of Parkinson's disease published between 2002 and 2005. Level I (randomized, controlled trial) reports of pharmacological, surgical, and nonpharmacological interventions for the motor symptoms of Parkinson's disease between January 2004 (2001 for nonpharmacological) and December 2010 were reviewed. Criteria for inclusion, clinical indications, ranking, efficacy conclusions, safety, and implications for clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
345
0
23

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(371 citation statements)
references
References 113 publications
(248 reference statements)
3
345
0
23
Order By: Relevance
“…Rotigotine was chosen as the candidate molecule for development since it is one of the most potent D2/D3 non-ergot agonists currently used clinically with proven safety and efficacy records in PD patients. 17,19,28 Rotigotine has essentially no oral bioavailability and is currently administered through the use of a daily transdermal patch. However, the patch often results in skin reactions and may fall off prematurely, leading to issues with patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Rotigotine was chosen as the candidate molecule for development since it is one of the most potent D2/D3 non-ergot agonists currently used clinically with proven safety and efficacy records in PD patients. 17,19,28 Rotigotine has essentially no oral bioavailability and is currently administered through the use of a daily transdermal patch. However, the patch often results in skin reactions and may fall off prematurely, leading to issues with patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Levodopa (in combination with a dopa decarboxylase inhibitor) is more efficacious but requires dosing intervals of 3 times per day initially. 16 The dose adjustments of dopamine agonists and levodopa preparations are made in response to clinical effect, emerging symptoms, and side effects. The risk of psychiatric side effects and dyskinesias is greater at higher doses, so a rule of thumb is to treat with the lowest dose possible to achieve benefits for the patient in terms of function and quality of life.…”
Section: Case 1-1mentioning
confidence: 99%
“…54,165 Paradoxically, a recent study demonstrated that neurosurgeons performed subthalamotomies as often as pallidotomies or thalamotomies in most or all of their cases. 85,145 It was shown that lesioning was more often offered to patients in countries with lower economical development or when patients financed their own surgeries.…”
Section: Subthalamotomy Versus Other Surgical Treatmentsmentioning
confidence: 99%